Hepatic Crtc2 controls whole body energy metabolism via a miR-34a-Fgf21 axis. Issue 1 (December 2017) - Han, Hye-Sook; Choi, Byeong; Kim, Jun; Kang, Geon; Koo, Seung-Hoi
Abstract Liver plays a crucial role in controlling energy homeostasis in mammals, although the exact mechanism by which it influences other peripheral tissues has yet to be addressed. Here we show that Creb regulates transcriptional co-activator (Crtc) 2 is a major regulator of whole-body energy metabolism.Crtc2 liver-specific knockout lowers blood glucose levels with improved glucose and insulin tolerance. Liver-specific knockout mice display increased energy expenditure with smaller lipid droplets in adipose depots. Both plasma and hepatic Fgf21 levels are increased inCrtc2 liver-specific knockout mice, as a result of the reduced miR-34a expression regulated by Creb/Crtc2 and the induction of Sirt1 and Pparα. Ectopic expression of miR-34a reverses the metabolic changes in knockout liver. We suggest that Creb/Crtc2 negatively regulates the Sirt1/Pparα/Fgf21 axis via the induction of miR-34a under diet-induced obesity and insulin-resistant conditions. CREB-regulated transcription coactivator 2, CRTC2, has been associated with regulation of glucose and lipid homeostasis. Here Han et al. show that Creb/Crtc2 modulates lipid and glucose metabolism by inhibiting the expression of mi-R34 that, in turn, represses the expression of Sirt1 and PPARα and consequently Fgf21 levels.